2015
DOI: 10.1007/s00167-015-3773-7
|View full text |Cite
|
Sign up to set email alerts
|

Double-row repair of the distal attachment of the superficial medial collateral ligament: a basic science pilot study

Abstract: The surgical technique adequately restored joint opening to an intact state with response to valgus stress. Agreement among surgeons when quantifying joint opening in mm was substantial. This paper addresses a technically difficult problem and provides pragmatic and practical information for surgeons who manage complicated multi-ligament knee injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Some differences between the results from the current study and those in the literature may be due to differences in loading. LaPrade et al [24] reported that gap width was measured during the application of a 10 Nm load, as in our study, whereas Kleinbaum and Blankstein [33] and Whelan et al [25] either did not control load or did not report it …”
Section: Figmentioning
confidence: 48%
See 4 more Smart Citations
“…Some differences between the results from the current study and those in the literature may be due to differences in loading. LaPrade et al [24] reported that gap width was measured during the application of a 10 Nm load, as in our study, whereas Kleinbaum and Blankstein [33] and Whelan et al [25] either did not control load or did not report it …”
Section: Figmentioning
confidence: 48%
“…This has clinical implications. For example, there is evidence that MCL-deficient knees show significantly greater values of absolute gap width compared with intact knees [24, 25, 33], and medial gap width may be a suitable method for assessing the efficacy of MCL repair [25]. Varus/valgus instability post-arthroplasty, which has been linked to patient satisfaction [11], and is often assessed clinically with radiographic examination, may also be possible to evaluate with ultrasound, though reverberation artifacts off of the metallic prosthesis [41] may make gap width measures more challenging in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations